2012
DOI: 10.3109/14992027.2012.700773
|View full text |Cite
|
Sign up to set email alerts
|

Audiometric screening of a population with intellectual disability

Abstract: KEY WORDSintellectual disability, screening audiometry, psycho-acoustic method Design: PTA was performed at six frequencies at the screening level 20 dB HL. Referral criteria were threshold levels ≥25 dB HL at two or more frequencies for one ear or both.Study sample: 1478 participants in ages 7-91 were included.Results: 1470 (99.5%) people cooperated in screening of which 1325 (90%) could be tested on both ears at all six frequencies. A majority, 987 (66.8%), performed ordinary PTA, 234 (15.8%) conditioned pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…These findings can be connected with data reported by DiGiovanni & Repka (2007), who obtained comparable and statistically insignificant different threshold levels across response modes at audiometric test frequencies in a typical population [12]. The comparable results of the current study are expected since audiometric procedures involve simple tasks that can be successfully and reliably performed by individuals having a mental age over 2½ years [18,[24][25].…”
Section: Discussionsupporting
confidence: 89%
“…These findings can be connected with data reported by DiGiovanni & Repka (2007), who obtained comparable and statistically insignificant different threshold levels across response modes at audiometric test frequencies in a typical population [12]. The comparable results of the current study are expected since audiometric procedures involve simple tasks that can be successfully and reliably performed by individuals having a mental age over 2½ years [18,[24][25].…”
Section: Discussionsupporting
confidence: 89%
“…However, much literature gave evidence to the contrary, including for those with severe or profound learning disabilities (Van Buggenhout et al ., ). It was suggested that the test method adopted is less important than its execution, that reducing anxiety and establishing trust are vital (Andersson et al ., ) and that, under the right conditions, the standard hearing test (pure tone audiometry) was possible for many of the population (Evenhuis, ).…”
Section: Resultsmentioning
confidence: 99%
“…The variety of hearing test methods chosen was largely determined by the extent of intellectual impairment in the populations studied; however, different forms of hearing assessment are not directly equivalent. Standard hearing assessment that involves the individual waiting for a sound, then responding in a repeatable way, tests the whole auditory pathway but was used as a diagnostic tool by only 2 studies (Buchanan, ; Van Buggenhout et al ., ), with a further 3 studies using this as a screening tool or in those that failed an earlier screen (Andersson et al ., ; Evenhuis, ; Meuwese‐Jongejeugd et al ., ). More objective measures that do not require the same level of compliance, such as auditory brainstem response testing (Evenhuis, ; Evenhuis et al ., ), are not representative of the whole auditory pathway and correction factors are required to give an estimate of true hearing levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations